Self-propagating high-temperature synthesis of Ti3AlC2 MAX phase from mechanically-activated Ti/Al/graphite powder mixture. Issue 8 (1st June 2018) - Akhlaghi, Maryam; Tayebifard, Seyed Ali; Salahi, Esmaeil; Shahedi Asl, Mehdi; Schmidt, Gert
Abstract: Titanium aluminum carbide was prepared employing the mechanically-activated self-propagating high-temperature synthesis process. The formation mechanism of Ti3 AlC2 MAX phase, synthesized using elemental titanium, aluminum, and carbon (graphite) powders via wave propagation and thermal explosion techniques, was investigated. The combustion reaction products were characterized by differential thermal analysis (DTA), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction analysis (XRD). Although Ti3 AlC2 was recognized as the dominant synthesis product, in both techniques, the formation of TiC was also verified as a byproduct. The MAX phase produced in the tubular furnace (thermal explosion mode) was purer than that synthesized in the reaction chamber (wave propagation mode). The results disclosed that the formation of TiC and TiAl compounds have significant roles on the combustion synthesis of Ti3 AlC2 MAX phase.